ANALISIS PENGARUH KUALITAS PRODUK, PROMOSI DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DENGAN CITRA MEREK SEBAGAI VARIABEL INTERVENING (Studi pada Konsumen Sepeda Motor Matic Merek Yamaha Mio di Kota Semarang) - Annisa Heny Yoepitasari; Imroatul Khasanah (Faculty of Economics and Business Diponegoro University, 2018)
The purpose of this research is to analyze the impact of product quality, promotion, and product design over buying decision through brand image in matic motorcycle yamaha mio brand in Semarang city. This research was conducted on consumers in the city of Semarang where the respondents had purchased Yamaha Mio brand motorcycle more than 1 time of purchase. The total of sample used in this research is 100 respondents with questionnaire as the collecting data method and non probability sampling as sampling method used with purposive sampling technique. The research used Structucal Equation Modelling as analyze technique which is estimated with SEM AMOS 21.0 program. The results of this study state that brand image has the most powerful and significant influence on purchasing decisions, followed by product quality, promotion and then product design which also has a strong and significant influence on brand image. Brand image factor is an important element that can influence buyer to make a purchase decision. So that the higher the level of brand image, the higher the decision to make purchases on these products and services.